Penerapan Media Wordwall Kuis Wordsearch untuk Meningkatkan Minat Belajar dan Keaktifan Siswa pada Materi Sistem Tata Surya Siswa Kelas VI - Putri Fajri Ma’wa; Panca Dewi Purwati (Jurnal Bintang Pendidikan Indonesia, 2024)
This study was motivated by the use of learning video-based media which turned out to be insufficient to increase student interest and activeness in learning Solar System material in grade VI. The purpose of this study was to determine how the application of Wordwall quiz wordsearch media in increasing student interest and activeness in Solar System material in grade VI. The research method used a descriptive qualitative approach with data collection techniques using observation, interviews, documentation, and questionnaires. The results of this study indicate an increase in student interest in learning and activeness as evidenced by the number of students who meet the learning interest indicators more than those who do not show interest in learning, namely many students show interest, a feeling of pleasure by answering that learning is unique and exciting, and their direct involvement with active in the application of Wordwall quiz wordsearch media in Solar System Material. In conclusion, students' learning interest and activeness can emerge and increase by practicing learning with Wordwall quiz wordsearch media that is interesting, exciting, and unique according to the indicators of learning interest and student activeness.